PENGELOLAAN AKUN SOSIAL MEDIA INSTAGRAM OPEN TRIP DAN JASA TITIP @jengmimarikmacitralestari DI ERA PANDEMI COVID-19 - Rini Anisyahrini; Winne Wardiani; Yanti Susilawati Tresnawati (Linimasa : Jurnal Ilmu Komunikasi, 2023)
The Covid-19 pandemic has changed life patterns, such as the tourism sector which has been badly affected due to restrictions on human movement. The Indonesian government implements IMR or New Habit Adaptation as an effort to keep active by implementing health protocols. Tourist trips by foreign tourists and domestic tourists have decreased as a result of restrictions on human movement and activity. Open Trip services and outward shopping entrusted services have decreased. However, tourism service actors and the creative economy must continue to maintain their business. Jastip and opentrip business owners in a state of survival continue to promote through social media. Open Trip business owners and Titip Services from the Instagram account @jengmimarikmacitralestari also carry out promotions on Instagram social media. The purpose of this research is to find out how to manage Instagram Open Trip accounts and Titip Services @jengmimarikmacitralestari in the Era of the Covid-19 Pandemic. The research method is qualitative with a case study research tradition approach. The case study on the Instagram account @jengmimarikmacitralestari is because there is a peculiarity of the case with the owner of the Instagram account Open Trip and Titip Service which is managed by the account owner who is very strong in promotion on Instagram social media. During the pandemic, it was a testing period for account owners in their business to be able to stay in business and continue to manage their Instagram accounts. The data collection technique is through in-depth interviews with the account owner, making observations on the Instagram social media account @jengmimarikmacitralestari, and literature review.